Akad Salam Menurut Fatwa DSN MUI Nomor 05/DSNMUI/IV/2000 - Pahra, Januara (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2022)
Salam buying and selling is a contract for buying and selling ordered goods between a buyer and a seller. The specifications and price of the ordered goods must have been agreed at the beginning of the contract, while payment is made in full in advance. Sale and purchase of greetings is a sale and purchase contract that is allowed. This is based on the arguments contained in the Qur'an. The pillars of salam are sellers and buyers, there are goods and money, there is sighat (lafaz contract). While the terms of sale and purchase of salam according to the agreement of the scholars there are five, namely the type of object of sale and purchase of greetings must be clear, the nature of the object of sale and purchase of greetings must be clear, the level or size of the object of sale and purchase of greetings must be clear, the period of ordering the object of sale and purchase of greetings must be clear, assumptions the capital issued must be known to each party.